Identification of Potential Signatures and Their Functions for Acute Lymphoblastic Leukemia: A Study Based on the Cancer Genome Atlas - Wang, Weimin; Lyu, Chunhui; Wang, Fei; Wang, Congcong; Wu, Feifei; Li, Xue; Gan, Silin (Frontiers in Genetics, 2021)
Objective: Acute lymphoblastic leukemia (ALL) is a malignant disease most commonly diagnosed in adolescents and young adults. This study aimed to explore potential signatures and their functions for ALL. Methods: Differentially expressed mRNAs (DEmRNAs), differentially expressed long non-coding RNAs (DElncRNAs) were identified for ALL from The Cancer Genome Atlas (TCGA) and normal control from Genotype-Tissue Expression (GTEx). DElncRNA-microRNA (miRNA) and miRNA-DEmRNA pairs were predicted using online databases. Then, a competing endogenous RNA (ceRNA) network was constructed. Functional enrichment analysis of DEmRNAs in the ceRNA network was performed. Protein-protein interaction (PPI) network was then constructed. Hub genes were identified. DElncRNAs in the ceRNA network were validated using Real time qPCR. Results: 2903 up- and 3228 down-regulated mRNAs and 469 up- and 286 down-regulated lncRNAs were identified for ALL. A ceRNA network was constructed for ALL, consisting of 845 lncRNA-miRNA and 395 miRNA-mRNA pairs. These DEmRNAs in the ceRNA network were mainly enriched in ALL-related biological processes and pathways. Ten hub genes were identified, including SMAD3, SMAD7, SMAD5, ZFYVE9, FKBP1A, FZD6, FZD7, LRP6, WNT1 and SFRP1. According to Real time qPCR, 8 lncRNAs including ATP11A-AS1, ITPK1-AS1, ANO1-AS2, CRNDE, MALAT1, CACNA1C-IT3, PWRN1 and WT1-AS were significantly up-regulated in ALL bone marrow samples compared to normal samples. Conclusion: Our results showed the lncRNA expression profiles and constructed ceRNA network in ALL. Furthermore, 8 lncRNAs including ATP11A-AS1, ITPK1-AS1, ANO1-AS2, CRNDE, MALAT1, CACNA1C-IT3, PWRN1 and WT1-AS were identified. These results could provide novel insight into the study of ALL.